Modelling and simulation of thermoelectric air cooling / Almujtaba Osama Ali Mohammed - Almujtaba Osama, Ali Mohammed (2018)
Thermoelectric cooling is a solid-state cooling technology that utilizing the Peltier effect to achieve a temperature difference between the two sides of the thermoelectric cooler (TEC). The basic principal which was discovered by Jean Peltier is that when current passed through a joint of two connected metals in an electric circuit, it will generate heat flux and the amount of the flux will depend on the Peltier coefficient of the two metals and the current passing through the circuit. The usage of this technology depends on the overall efficiency of the cooling system and that in turn depends on the thermal efficiency of that system. The objective of this study is to model and simulate a simplified application specific system that will allow to monitor the changes in the efficiency of the system. Ansys fluent has been used to investigate the effect of different design parameters like the flow rate, heat flux and geometry on the outlet temperature. An ideal thermoelectric cooler has been represented as a source of constant heat flux, assuming an element with constant properties during operation at all operation conditions. The outlet air mean temperature has been used as an indication for both of efficiency and effectiveness because at the same input temperature and heat flux the only variable affecting them will be outlet mean temperature. The simulation results show that increase of the system cooling power results in higher heat flux and higher temperature difference between the air inlet and the outlet temperatures, but it’s not the most efficient way to lower the outlet air temperature as the increase in the power input will result in lower coefficient of performance. At the same time the decrease in the flow rate by lowering the inlet air velocity results in a significant change in the temperature difference without the need of extra work to be done. Similarly, the shape of inner wall surface had a slight effect on the temperature difference. In the future a more realistic model of the thermoelectric cooler can be used allowing to accurately measure the coefficient of performance with respect to the actual power used by the element. Also, geometry is an important parameter that need to be further investigated. Keywords: Thermoelectric, Cooling, Modelling, Simulation